The elimination of anticipated written errors from L1 interference through flipped classrooms - Napacha Prapawadee (Journal of Research on English and Language Learning (J-REaLL), 2021)
Several studies have been conducted on written errors discovered in an EFL classroom, and the findings are similar, and that common errors have been discovered in Thai students’ written work, so these studies conclude that the main cause of errors is L1 interference.  In addition, other related studies reveal that flipped classrooms can support students’ learning process.  It is due to the fact that these days, EFL students still have problems with some grammatical aspects due to their mother tongue, and the class time provided is limited.  Therefore, to ascertain that the flipped classroom can help eliminate the anticipated grammatical problems repeatedly in class; the study looks to develop online lessons on LMS to encourage the students to learn at their own pace and to engage students with class activities.  The online lessons and class activities are currently being implemented, and 25 freshmen participate in this study.  The questionnaire will be completed at the end of the semester to discover their attitudes towards the flipped classroom covering online lessons and class activities.  Also, a pre-test and post-test on simple sentences are used to investigate the students’ learning outcomes via the flipped classroom.  The findings from the pre- and post-tests confirm the results of the former studies that the students produce the anticipated errors such as articles, capitalization, punctuation, nouns, and subject-verb agreement.  Also, synchronous and asynchronous learning can help eliminate those mentioned errors and the students have positive attitudes towards the flipped classroom.Keywords: written errors; L1 interference; flipped classroom